2015
DOI: 10.5489/cuaj.2848
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes following laparoscopic management of pT3 renal masses: A large, multi-institutional cohort

Abstract: Introduction: We described the clinical and oncological outcomes of patients treated by laparoscopic surgery for non-metastatic pT3 renal cell carcinoma (RCC). Methods: We queried a multi-institutional database for patients diagnosed with non-metastatic pathological T3 RCC from 13 Canadian centres treated laparoscopically (radical or partial nephrectomy) between 2008 and 2014. Clinical and pathological outcomes were evaluated. Progression was defined as the development of recurrence or metastatic disease. Log-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Multivariate analysis confirmed that RN and pT3 stages were the predictors of overall mortality. The present results showed that non-metastatic pT3 RCC after laparoscopic management incurred metastatic progression of 26% and the three-year mortality rate was 33%(46). A study by Leibovich et al(47) has shown that the risk ratio for death is 1.87 times higher in patients with peripheral perinephric or renal sinus fat invasion compared with those without fat invasion (p <0.001).…”
supporting
confidence: 47%
“…Multivariate analysis confirmed that RN and pT3 stages were the predictors of overall mortality. The present results showed that non-metastatic pT3 RCC after laparoscopic management incurred metastatic progression of 26% and the three-year mortality rate was 33%(46). A study by Leibovich et al(47) has shown that the risk ratio for death is 1.87 times higher in patients with peripheral perinephric or renal sinus fat invasion compared with those without fat invasion (p <0.001).…”
supporting
confidence: 47%
“…The Canadian Kidney Cancer information system (CKCis) is a collaborative multi-institutional database from 13 centers in 6 provinces and has been described previously. [18][19][20] This dataset was initiated in 2011 and includes data entered retrospectively and prospectively for a sample of patients with renal tumors treated as of 1998. Demographic, clinical, pathological, and oncological variables are collected and the dataset is updated regularly.…”
Section: Methodsmentioning
confidence: 99%
“…43 patients had distant metastasis and 3 patients had local recurrence. 6 patients died due to kidney cancer [15]. In another study involving 94 patients who underwent LRN for locally advanced disease, the follow-up period was 24.8 months.…”
Section: Resultsmentioning
confidence: 99%
“…Nayak, et al shared the results of 176 T3 RCC patients who underwent laparoscopic surgery. They reported the mean tumor size of 7 cm, the mean operation time of 124 min, and the mean estimated blood loss of 150 cc [15]. The mean operative time of the patients who underwent LRN for 94 locally advanced RCC was 150 minutes, the mean estimated blood loss was 100 cc, the conversion from laparoscopic to open surgery was 6.4%, and the hospital stay was 5 days [16].…”
Section: Discussionmentioning
confidence: 99%